Financial Performance Analysis of Dividends on the LQ45 Index - Maulana, Muhamad Azril; Pratama, Muhamad Davala Hadi; Akram, Arie Muhamad; Giovansyah, Reihan Yusuf; Leon, Farah Margaretha (Universitas Proklamasi 45, 2024)
Dividend policy is a company's decision to distribute profits between shareholders and the company itself. This study aims to evaluate the influence of factors that determine dividend policy. The independent variables in this study include profitability, leverage, firm size, liquidity, firm age, corporate taxes, and growth opportunities, while the dependent variable is the managed dividend policy. Processed using table data. The limitation of the problem in this study is that by LQ45 index, we mean companies listed on the LQ45 index in the period 2022 and distributing dividends in the five year (2018-2022). The goal of the research is to see the influence of factors that determine dividend policy. The results of the conducted research show that liquidity and age of the company do not affect dividends. Profitability and debt have a significant negative impact on dividend policy. The size of the company, growth opportunities, and corporate tax then have a significant positive impact on dividends. The significance of the conducted research is to guide bank managers in re-evaluating the level of profitability and leverage used, as well as paying attention to the management of growth opportunities, tax, and regulatory aspects. Company's scale provide higher dividends.